Prevalence of Candidal Carriage Rate in Denture Wearers and Evaluation of the effect of Whole Unstimulated Salivary Flow Rate and pH of Saliva on their Carriage Rates - Ashita R Kalaskar; Shirish Degwekar (Wolters Kluwer Medknow Publications, 2010)
Objectives: To assess the prevalence of Candida carriage rate in denture wearers and to evaluate the effects of local factors and habits of tobacco and betelnut on Candida carriage rate. Study design: 60 edentulous subjects and 60 dentulous subjects were evaluated. Standard methods for culture, salivary flow rates and pH determination were used. Statistically analysis was carried out using Students unpaired "t" test, 'Chi square test, z-test, ANOVA F-test and Tukey multiple comparison test. Results: Highest prevalence of Candida carriage rate was shown by group 1 (63.33%). The mean whole unstimulated salivary flow rate (p < 0-01) and pH (p < 0.05) were less in the subjects showing positive candida culture. Significant (p < 0.05) increase in prevalence of Candida carriage rate was found in subjects wearing prosthesis and having habits. Conclusion: The prevalence of Candidal carriage rate in healthy individuals increased in the presence of prosthesis and decreased salivary flow rate and pH.